2022
DOI: 10.3390/app12178886
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Counting Point Detector for Nanosecond Coherent X-ray Science

Abstract: We present the technical realization of a high-speed hard X-ray single-photon counting-detection scheme based on a commercial avalanche silicon photodiode and high-speed oscilloscope. The development is motivated by the need to perform pulse-resolved photon-correlation and pump-probe studies at synchrotron sources with densely packed pulse patterns that result in high repetition rate pulses on the order of hundreds of MHz. Commissioning experiments are performed at the 1C PAL-KRISS beamline at PLS-II of South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Lee at al. reported on the technical realization of a high-speed hard X-ray single photon detection scheme at a synchrotron that delivers X-ray pulses at a repetition rate of 500 MHz [3]. Sung et al reported on the development of a single-shot coherent X-ray imaging instrument at Pohang Accelerator Laboratory that is optimized to perform XPCS, CDI, and coherent X-ray scattering experiments for pursuing ultrafast phenomena of nanoparticles [4].…”
mentioning
confidence: 99%
“…Lee at al. reported on the technical realization of a high-speed hard X-ray single photon detection scheme at a synchrotron that delivers X-ray pulses at a repetition rate of 500 MHz [3]. Sung et al reported on the development of a single-shot coherent X-ray imaging instrument at Pohang Accelerator Laboratory that is optimized to perform XPCS, CDI, and coherent X-ray scattering experiments for pursuing ultrafast phenomena of nanoparticles [4].…”
mentioning
confidence: 99%